Transmissão oportunística de informação em redes veiculares - Tavares, Bruno Miguel Pinho (2013)
The area of wireless communications has been the subject of several research projects over the last years. The persistent need to ”communicate” in various environments, including high mobility, make the use of wirelessbased communications a strong requirement. In this context, VANETs were created, which are networks based on Ad Hoc concept allowing the communication between vehicles and between vehicles and fixed infrastructures, that increase network’s connectivity. VANETs, due to their characteristics, introduce challenges such as shorts connectivity intervals in sparse networks, and also in situations where connectivity can be down for long periods of time. The work of this Dissertation aims to send non-urgent information in a opportunistic way, maximizing the network resources. The DTN’s concept is thus addressed as a solution to the previous described challenges. Two DTN implementations are studied and tested to be incorporated in WAVE devices communicating using the standard IEEE 802.11p for vehicular networks. After several tests, IBR-DTN proved to be the most robust and ”light” implementation to be used in embedded systems, such as the OBUs used in VANETs. Several implementation problems were detected, through several tests, and corrected to be possible to provide the functional integration of IBR-DTN in a real vehicular environment. The set of tests consisted in: two scenarios in the laboratory environment, to better understand IBR-DTN’s operation; and three scenarios in a real testbed with vehicles and fixed stations. The two scenarios tested in laboratory allowed to conclude the good performance of fragmentation process for different connection time intervals and different file sizes, where the connections between the nodes were periodically interrupted. The scenarios performed on the real testbed show that IBR-DTN operates without problems for various velocities using fixed infrastructures and a car, and two cars moving towards each other in different ways. It can be also concluded that, increasing the velocity, the contact time between nodes decreases, contributing to a larger number of fragments needed to send a specific file. The results show also that IBR-DTN has a good response in high mobility environments like VANETs.